Does CSRD moderate the effect of financial performance on stock return? Evidence of Indonesian mining companies - Dody Hapsoro; Crescentiano Agung Wicaksono; Theodora Anindita Primaretka (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2020)
The purpose of this study is to examine the effect of financial performance on stock returns with corporate social responsibility disclosure as a moderating variable in mining companies listed on the Indonesia Stock Exchange (IDX) 2014-2016 period. This study used multiple linear regression to examine the corporate social responsibility disclosure in moderating the effect of financial performance on stock returns. The measurement of financial performance uses financial ratios, namely return on equity. The test results showed that partial return on equity had a positive and significant effect on stock returns. Furthermore, corporate social responsibility disclosure strengthens the effect of return on equity on stock returns. The implication of this research is for potential investors who want to invest in stocks should consider more disclosure of corporate social responsibility, because disclosure of corporate social responsibility is proven to be able to strengthen the effect of return on equity on increasing stock returns.